Pendapatan dan Kelayakan Usahatani Padi Sawah Tadah Hujan Kabupaten Bone - Fattah, Muhammad Arifin; Arifin, Arifin; Sadat, Mohammad Anwar; Azisah, Azisah; Megawati, Megawati; Jumiati, Jumiati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Farmers' income levels are generally influenced by components, namely: the amount of production, selling prices, and costs incurred by farmers in their agriculture. Generally, the characteristics of farming in Indonesia are narrow land, relatively small capital, limited knowledge of farmers, and less dynamic which results in low farm income. Feasibility studies need to be carried out to avoid capital that is too large for an activity that turns out to be unprofitable. The purpose of this study was to analyze the income and feasibility of rainfed rice farming in Talabagi Village, Patimpeng District, Bone Regency, South Sulawesi. The study was carried out in January - March 2023. The population of this study was rainfed rice farmers, totaling 300 families. The number of samples is 10% of the total population of 30 farmers. Farmers' samples were taken using a simple random sampling method. Data collection techniques used in this study were observation, interviews, and documentation. The types of data in this study are qualitative data and quantitative data. There are two sources of data, namely primary and secondary data. The data analysis method used in this research is descriptive quantitative. Data were analyzed by income and feasibility analysis. The results showed that the average income received by farmers in rainfed lowland rice farming in Talabagi Village, Patimpeng District, Bone Regency was Rp. 11,081,258.61/MT. Rainfed lowland rice farming carried out by farmers in Talabagi Village, Patimpeng District, Bone Regency is feasible.